Administered Paricalcitol Dose and Survival in Hemodialysis Patients: A Marginal Structural Model Analysis - Miller, Jessica E (Pharmacoepidemiol Drug Saf, 2012)
PURPOSE: Several observational studies have indicated that vitamin D receptor activators (VDRA), including paricalcitol, are associated with greater survival in maintenance hemodialysis (MHD) patients. However, patients with higher serum parathyroid hormone (PTH), a surrogate of higher death risk, are usually given higher VDRA doses, which can lead to confounding by indication and attenuate the expected survival advantage of high VDRA doses. METHODS: We examined mortality-predictability of low (>1 but <10 μg/week) versus high (≥10 μg/week) dose of administered paricalcitol over time in a contemporary cohort of 15,442 MHD patients (age 64±15 years, 55% men, 44% diabetes, 35% African Americans) from all DaVita dialysis clinics across the USA (7/2001-6/2006 with survival follow-ups until 6/2007) using conventional Cox regression, propensity score (PS) matching, and marginal structural model (MSM) analyses. RESULTS: In our conventional Cox models and PS matching models, low dose of paricalcitol was not associated with mortality either in baseline (hazard ratio (HR): 1.03, 95%confidence interval (CI): (0.97-1.09)) and (HR: 0.99, 95%CI: (0.86-1.14)) or time-dependent (HR: 1.04, 95%CI: (0.98-1.10)) and (HR: 1.12, 95%CI: (0.98-1.28)) models, respectively. In contrast, compared to high dose of paricalcitol, low dose was associated with a 26% higher risk of mortality (HR: 1.26, 95%CI: (1.19-1.35)) in MSM. The association between dose of paricalcitol and mortality was robust in almost all subgroups of patients using MSMs. CONCLUSIONS: Higher dose of paricalcitol appears causally associated with greater survival in MHD patients. Randomized controlled trials need to verify the survival effect of paricalcitol dose in maintenance hemodialysis patients are indicated.